2014
DOI: 10.1007/s12013-014-0062-x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of MicroRNA-122 Re-sensitizes 5-FU-Resistant Colon Cancer Cells to 5-FU Through the Inhibition of PKM2 In Vitro and In Vivo

Abstract: 5-Fluorouracil (5-FU) is one of the most commonly used anticancer drugs in the treatment of colon cancer. However, acquired chemoresistance is becoming one of the major challenges for patients with advanced stages of colon cancer. Currently, the mechanisms underlying cancer cell resistance to 5-FU are not fully understood. MicroRNAs (miRNA) have been suggested to play important roles in tumorigenesis and drug resistance in colon cancer. In this study, we generated 5-FU-resistant colon cancer cell lines from wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 19 publications
5
53
0
Order By: Relevance
“…For instance, Li et al showed that miR-218 functions synergistically with 5-FU to promote chemosensitivity by suppressing BIRC5 and TS in CRC [22]. He et al showed that overexpression of miR-122 re-sensitizes 5-FU-resistant CRC cells to 5-FU through the inhibition of PKM2 in vitro and in vivo [23]. Similarly, other miRNAs are reported to induce the 5-FU resistance of CRC cells.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Li et al showed that miR-218 functions synergistically with 5-FU to promote chemosensitivity by suppressing BIRC5 and TS in CRC [22]. He et al showed that overexpression of miR-122 re-sensitizes 5-FU-resistant CRC cells to 5-FU through the inhibition of PKM2 in vitro and in vivo [23]. Similarly, other miRNAs are reported to induce the 5-FU resistance of CRC cells.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-23 expression was also discovered to undermine 5-FU-induced apoptosis by regulating apoptosis-activating factor-1 (APAF-1)/caspase-9 apoptotic pathway [8]. On the contrary, other miRNAs, such as miR34a [9], miR-122 [10], and miR-129 [11], were revealed to enhance the cytotoxic effect of 5-FU via the down-regulation of Sirt1 and E2F3 [12], PKM2 [13], and B cell lymphoma 2 (BCL2) [14], respectively. These miRNAs mainly exert their functions by affecting the apoptosis signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…miR-26a regulates glucose metabolism of CRC cells by directly targeting PDHX, which inhibits the conversion of pyruvate to acetyl coenzyme A in the citric acid cycle (41). He et al (46) reported that overexpression of miR-122 in fluorouracil (5-FU)-resistant cells resensitizes 5-FU resistance through the inhibition of PKM2 in vitro and in vivo . Furthermore, glucose metabolism is significantly upregulated in 5-FU-resistant cells.…”
Section: Numerous Novel Glucose Metabolism Mechanisms Involve Mirna Rmentioning
confidence: 99%